2018
DOI: 10.14196/mjiri.32.34
|View full text |Cite
|
Sign up to set email alerts
|

A double blind randomized clinical trial to investigate the effect of vitamin D supplementation on metabolic and hepato-renal markers in type 2 diabetes and obesity

Abstract: Background: According to the recent studies, vitamin D deficiency has been correlated with progress in type 2 Diabetes and Metabolic Syndrome. The aim of this study was to assess the effect of vitamin D supplementation on glucose and lipid profiles, blood pressure, and biomarkers of liver and kidney in type 2 diabetic patients. Methods: In this Double blinded randomized clinical trial, 90 patients with type 2 diabetes and serum 25-Hydroxy vitamin D levels of less than 30 ng/ml recruited from "Besat Diabetes C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Detailed characteristics of included studies are presented in Table 1 . Overall, most of the studies (n = 13) were conducted in Asia ( 12 , 26 , 29 , 30 , 32 , 33 , 35 , 37 39 , 41 , 42 , 44 ). Thirteen studies clarified using vitamin D3 as their supplementation ( 12 , 26 – 32 , 34 36 , 40 , 43 ), while the remaining 7 studies did not specify the type of vitamin D ( 33 , 37 39 , 41 , 42 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed characteristics of included studies are presented in Table 1 . Overall, most of the studies (n = 13) were conducted in Asia ( 12 , 26 , 29 , 30 , 32 , 33 , 35 , 37 39 , 41 , 42 , 44 ). Thirteen studies clarified using vitamin D3 as their supplementation ( 12 , 26 – 32 , 34 36 , 40 , 43 ), while the remaining 7 studies did not specify the type of vitamin D ( 33 , 37 39 , 41 , 42 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-eight articles were assessed for eligibility, and an additional 68 studies were excluded due to the following reasons: lacked information on lipid profiles, usage or doses of vitamin D supplementation, baseline 25OHD or BMI, or administration of vitamin D fortification (n = 47); inappropriate control or intervention group (n = 20); not mention the specific type of diabetes (n = 1). Finally, 20 articles with 24 effect sizes were included (12,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Study Selectionmentioning
confidence: 99%
“…Otherwise, VD supplementation enhanced the anti-inflammatory endogenous mechanisms in the kidney in different diseases (51,52) .…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in line with previous reports, that showed significant reduction in MDA levels, as well as the proinflammatory cytokines IL1β, IL6, IFN-γ and IL17A in paracetamol group. The hepatic and renal tissue proteins of the GPx enzymes in addition to the anti-inflammatory cytokine IL10 (38,51) . Moreover, Vitamin-D correlated significantly and positively with the antioxidative indicators and anti-inflammatory cytokines, whereas inverse significant correlations were observed with the pro-oxidant and proinflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study showed that coronary syndrome patients with low serum 25 (OH)D levels had a higher incidence of in-hospital complications and mortality [ 31 ]. Another study recruited 90 T2DM patients with serum 25 (OH)D levels less than 30 ng/ml, added 50000 IU vitamin D for eight weeks, and results showed a significant increase in serum vitamin D levels, decrease in serum HbA1c levels, and increase in HDL-cholesterol levels [ 32 ]. This experiment proved that vitamin D supplements can improve HbA1c and lipid metabolism in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%